Augmented reality in science learning: A systematic literature review - Z. Zufahmi; Fatchur Rohman; Murni Sapta Sari (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Augmented reality (AR) is one of the technologies that can be integrated in learning. However, more in-depth information on the advantages of AR is still needed. This systematic review aims to review various studies on AR in science learning and the positive impact of its use that have been published in Scopus indexed journals. The inclusion and exclusion model used is PRISMA. This SLR uses 44 articles found in Scopus indexed journals in 2019-2023. These studies are original articles published in English and are open access.  The results of this study show an increase in AR research in science learning. AR research in the field of science learning is most dominantly carried out using a quasi-experimental approach. There are five countries that have the most publications on the theme of AR. Augmented Reality has been widely implemented at various levels of education and makes a positive contribution to learning. The positive impact of using AR can improve visualization, motivation, learning experience, and student personnel in science learning. Based on the research results, it can be concluded that the focus of AR will continue to grow in the modern era supported by technological advances. This trend is reflected in the distribution of year, authors, keywords, research types/methods, author nationality, and international collaboration.